Numerical study three-dimensional of mixed convection in a cavity: Influence of Reynolds and Grashof numbers - Razik, Benderradji (Université de M'sila, 2018)
In this work, we present a numerical study of mixed convection heat exchange in a cubic cavity of a laminar three-dimensional (3D) incompressible flow. This study predicted the behavior of the flow structure between Multi clear structure dominated by natural convection when the Reynolds number is small, and a Multi clear structure dominated by forced convection when the Reynolds number is high. First, we fix the Grashof number for the variable Reynolds number. Second, we vary the number of Grashof for which the Reynolds number is kept fixed. The results obtained give a clear comparison with those found in the literature it examines and explains the thermal and dynamic characteristics of the flow.
Journal of Advanced Research in Fluid Mechanics and Thermal Sciences
Keywords: mixed convection, cavity,multi clear structure, number of Grashof and Reynolds